An experience on the content of teaching work - Falcón Armas, Andrés; Saavedra Rodríguez, Sonia; Lázaro Rodríguez, María Rosa (Avances en Supervisión Educativa, 2009)
When teaching the basic skills of a curriculum it seems obvious that teachers should employ professional expertise that allows their students to acquire new abilities. This article outlines an experiment carried out in a learning centre in which school officials and teaching staff along with external advisors examined the problem of how these basic skills can be imparted if the pedagogy employed has not been designed using new teaching skills. Through the experiment, which was not without its ups and downs, a professional skills inventory was established to improve pedagogical organisation, teacher performance and evaluation of the teaching. The article describes the process which led to these professional teaching skills being incorporated into the centre’s mission statement.